Wellbore cement alteration during decades of abandonment and following CO2 attack – A geochemical modelling study in the area of potential CO2 reservoirs in the Pannonian Basin. (February 2020) - Szabó-Krausz, Zsuzsanna; Gál, Nóra Edit; Gável, Viktória; Falus, György
Abstract: In East-Central Europe, the sedimentary rocks and saline reservoirs of the Pannonian Basin provide the greatest potential for geological sequestration of CO2 . However, there is no knowledge about the integrity of cement casing and plugs in abandoned wellbores drilled in the last century, which surround the potential CO2 geological storage sites. Thermodynamic and kinetic batch, and 1D kinetic reactive transport models have been built up in PHREEQC to estimate the present composition of hydrated cement in different depths (106, 1478, 2136 and 2718 m) of these abandoned wellbores and, to access cement reactivity for the effect of potentially injected CO2 . The wellbore cements are all predicted to presently consist of mainly calcium silicate hydrate (CSH) and portlandite but differences occur due to the stability of ettringite connected to the temperature of the geological environment. With the depth, the amount of potentially dissolved CO2 increases which induces the breakdown of portlandite and CSH in the cement, and the major precipitation of calcite and amorphous silica. The transformation affects the whole width of the cement casing after about 2–3 years in most of the depths. However, the calculated mass transfer among minerals indicate a 2–6% porosity drop, which raises the attention to potential pore clogging. This process significantly reduces the risks of abandoned wellbores when implementing CO2 geological storage. Highlights: CO2 leakage risk through abandoned wellbores in the Pannonian Basin is studied. PHREEQC models are used for predicting geochemical interactions. The present compositions of 60 years old cements in different depths are estimated. The interactions of hydrated cements and potentially injected CO2 are accessed. Porosity changes in the 5 cm width cement casing are calculated at different depths.